Relasi Islam dan Negara dalam Bingkai Keindonesiaan - Muhammad, Ali Rasyidi; M, Misbahuddin; Suhufi, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Islam is not only a religion but also Islam has a political ideology that can be guided in state life, the Prophet Muhammad saw is not only a prophet and messenger sent to deliver the message of the holy message but he is also a leader of the state of Medina who made the Qurâ€™an as a law and the Arabian Peninsula as his territory and the city of Medina as the center of his government,Â However, there are also groups from the Islamic community who want to limit the role of the Prophet and consider the Prophet Muhammad saw only a prophet and messenger who delivered a treatise to his people no more than that, in the context of Indonesia the tug-of-war between Islamic nationals and secular nationalists existed before this nation became independent, The tug-of-war continues even after the country has a constitution, the struggle has moved from the realm of the constitution to the realm of its application. This paper tries to examine the relationship between religion and state in the frame of Indonesia, This study aims to describe how the relationship between religion and state in general and Indonesia in particular, The method used in obtaining data is a descriptive method through literature study.